2013
DOI: 10.1111/bij.12006
|View full text |Cite
|
Sign up to set email alerts
|

Very fine-scale population genetic structure of sympatric asterinid sea stars with benthic and pelagic larvae: influence of mating system and dispersal potential

Abstract: The present study investigated the fine‐scale population genetic structure of sympatric asterinid sea stars with contrasting modes of larval development (benthic versus pelagic). Parvulastra exigua lacks a dispersive life phase yet is one of the worlds most widely distributed and abundant sea stars, whereas Meridiastra calcar, a sea star with a dispersive larva, has a more limited regional scale distribution. Populations of P. exigua sampled from tide pools on three adjacent headlands showed significant geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 114 publications
(200 reference statements)
5
35
0
Order By: Relevance
“…Life history characteristics influence the genetic structuring of marine invertebrate populations (Barbosa, Klanten, Puritz, Toonen, & Byrne, 2013;Bohonak, 1999;Hart & Marko, 2010;Pelc, Warner, & Gaines, 2009). Many marine invertebrates have a biphasic life cycle composed of a pelagic larval phase and a sessile adult stage (Pusack, Christie, Johnson, Stallings, & Hixon, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life history characteristics influence the genetic structuring of marine invertebrate populations (Barbosa, Klanten, Puritz, Toonen, & Byrne, 2013;Bohonak, 1999;Hart & Marko, 2010;Pelc, Warner, & Gaines, 2009). Many marine invertebrates have a biphasic life cycle composed of a pelagic larval phase and a sessile adult stage (Pusack, Christie, Johnson, Stallings, & Hixon, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Variation in larval dispersal and reproductive traits can affect the degree and scale of population genetic structure (Barbosa et al, 2013;Kamel, Hughes, Grosberg, & Stachowicz, 2012). For instance, various studies have shown that the absence (direct development) or the presence of a larval phase (indirect development)…”
Section: Introductionmentioning
confidence: 99%
“…Hermaphroditism and benthic brood protection have evolved in parallel as a suite of life-history traits among multiple asterinid lineages [14], in physiologically extreme high-intertidal habitats and in association with low genetic diversity and strong population differentiation [15]. The apparent ease with which many asterinid lineages can evolve benthic brood protection and self-fertility [20] raises the question of why such lineages have not replaced asterinids with gonochoric outcrossing adults and planktonic larvae? One hypothesis involves the associated high risk of local extirpation and extinction.…”
Section: Discussionmentioning
confidence: 99%
“…KC866341-42) and two parts of the mitochondrial genome concatenated together as a single locus (several transfer RNA genes plus the control region) [21,22] (KC876801-859). All nine loci are highly variable in other asterinids, including P. exigua [10,19,20]. We used some of the same microsatellite markers to genotype offspring and brooding females from four populations (The Granites, Smooth Pools, Eaglehawk Neck, The Blowhole; table 1) to look for evidence of sexual reproduction and outcrossing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation